Application of FE-SEA hybrid method in vibro-acoustic environment prediction of complex structure. (September 2016) - Qin, Z H; Zhang, Z P; Ren, F; Li, H B; Liu, Z H; Zhang, Z; Yuan, K; Wang, Y C
Abstract: Spacecraft sustains the complex and severe vibro-acoustic environments during the flight. Acoustic test is different from random vibration test, but they can complement the energy in different frequency band for each other. Vibro-acoustic environment prediction of structure can provide supports for measuring point arrangement and test condition defining. In this paper, the application of FE-SEA hybrid method in vibro-acoustic environment prediction of complex structure is studied. Structural response is predicted through reasonable loading method and modelling method. Vibro-acoustic test results show the validity of the prediction method.